New Insights into Mechanisms of Cardioprotection Mediated by Thyroid Hormones. (10th March 2013) - Nicolini, G.; Pitto, L.; Kusmic, C.; Balzan, S.; Sabatino, L.; Iervasi, G.; Forini, F.
Abstract : Heart failure represents the final common outcome in cardiovascular diseases. Despite significant therapeutic advances, morbidity and mortality of heart failure remain unacceptably high. Heart failure is preceded and sustained by a process of structural remodeling of the entire cardiac tissue architecture. Prevention or limitation of cardiac remodeling in the early stages of the process is a crucial step in order to ameliorate patient prognosis. Acquisition of novel pathophysiological mechanisms of cardiac remodeling is therefore required to develop more efficacious therapeutic strategies. Among all neuroendocrine systems, thyroid hormone seems to play a major homeostatic role in cardiovascular system. In these years, accumulating evidence shows that the "low triiodothyronine" syndrome is a strong prognostic, independent predictor of death in patients affected by both acute and chronic heart disease. In experimental models of cardiac hypertrophy or myocardial infarction, alterations in the thyroid hormone signaling, concerning cardiac mitochondrion, cardiac interstitium, and vasculature, have been suggested to be related to heart dysfunction. The aim of this brief paper is to highlight new developments in understanding the cardioprotective role of thyroid hormone in reverting regulatory networks involved in adverse cardiac remodeling. Furthermore, new recent advances on the role of specific miRNAs in thyroid hormone regulation at mitochondrion and interstitial level are also discussed.